1999
DOI: 10.1177/10778019922181149
|View full text |Cite
|
Sign up to set email alerts
|

A Routine Activity Theory Explanation for Women's Stalking Victimizations

Abstract: Drawing on surveys administered to 861 university women in nine institutions, this article presents a routine activity theory model for predicting stalking victimization likelihood for women. Using routine activity theory, the model highlights lifestyle behaviors and interactions as predictors of stalking victimization. Whereas routine activity theory often highlights the role of demographics and statuses as predictors, this analysis emphasizes the role of women's social interactions and substance use in victi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
165
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(174 citation statements)
references
References 25 publications
7
165
0
2
Order By: Relevance
“…Therefore, a number of social researchers have used definitions provided by victims to measure and understand stalking victimisation (Emerson et al, 1998;Mustaine and Tewksbury, 1999). The study on which this article is based also relied on the understandings of participants about what stalking is based on their experiences thus aiming to capture a wide range of experiences and interpretations on the nature of stalking victimisation.…”
Section: Conceptualising Defining and Criminalising Stalking Definitmentioning
confidence: 99%
“…Therefore, a number of social researchers have used definitions provided by victims to measure and understand stalking victimisation (Emerson et al, 1998;Mustaine and Tewksbury, 1999). The study on which this article is based also relied on the understandings of participants about what stalking is based on their experiences thus aiming to capture a wide range of experiences and interpretations on the nature of stalking victimisation.…”
Section: Conceptualising Defining and Criminalising Stalking Definitmentioning
confidence: 99%
“…In the National Violence Against Women study, Tjaden and Thoennes (1998) found that over half of stalking victims reported being between 18 and 29 years of age, the typical time span of college years. And indeed, prevalence rates coming out of studies on university campuses range from 6 to 41% of college students (Coleman, 1997;Jordan et al, 2007;Levitt, Silver, & Franco, 1996;Logan, Leukefeld, & Walker, 2000;McCreedy & Dennis, 1996;Mustaine & Tewksbury, 1999;Spitzberg & Rhea, 1999;Tjaden, 2003;Tjaden & Thoennes, 1998). In more recent years, technology-based coercive behavior has come with the growth of technology and social networking (Jones, Mitchell, & Finklehor, 2012;Thompson & Morrison, 2013).…”
mentioning
confidence: 99%
“…In other words, the closer the victim and the offender are in distance, the higher the probability that a crime may occur (De Coster, Estes, & Mueller, 1999;Landau & Bendalak, 2008;Lynch, 1987;Madriz, 1996;Miethe & Meier, 1990;Mustaine & Tewksbury, 1999;Wittebrood & Nieuwbeerta, 2000;Wooldredge, Cullen, & Latessa, 1992). Further, the proximity of the target to high crime areas increases to opportunity for crime to occur (Meier & Miethe, 1993).…”
Section: Chapter III Routine Activities Theorymentioning
confidence: 99%
“…According to Brown and others (2015), "there must be something that tempts the hedonistic calculus of the would-be offender" (Brown, Esbensen, & Geis, 2015, p. 189). According to Mustaine and Tewksbury (1999), this attractiveness can also be seen as vulnerability when the target is a woman.…”
Section: Chapter III Routine Activities Theorymentioning
confidence: 99%